CRITERIA AND DIAGNOSTIC TOOLS FOR MONITORING QUALITY ASSESSMENT OF PRE-SERVICE TEACHERS' TRAINING FOR PRACTICE-ORIENTED RESEARCH ACTIVITY - Tamara А. Strokova (Russian State Vocational Pedagogical University, 2016)
The purpose of the present publication is to disclose the contents of the monitoring initial stage including theoretical understanding of observed object, comprehension of its essence, definition of assessment criteria, the choice of diagnostic means and sources of information. Methods. The problem analysis of scientific prerequisites for pedagogical interpretation of education quality phenomenon, comparison and assessment of various approaches in definition of its essence are carried out from the system approach; the author's understanding of quality of future teachers training to research activity and criteria of its assessment is proved. The studying and analysis of official documents, educational programs and scientific publications, systematization, substantial generalization, structuring, differentiation and expert assessment are used while the problem solution of main research actions for scientific and pedagogical search selection, which are essential result of high school training. Results. Criteria and estimated complex of quality of learners training to research activity, developed according to requirements of the monitoring assessment, reflecting its intrinsic properties (quality of educational process, quality of its conditions, quality of the received results) and their specific indicators are proposed. Stage-by-stage procedure of research actions selection is developed. Diagnostic means and sources of information are defined. Scientific novelty. Definition of the concepts «education quality», in terms of its understanding as a set of intrinsic aspect characteristics and the quality principle of process and its conditions quality reflection (A. I. Subetto), and the «practice-oriented research activity» defined as a set of the research actions reflecting its subject contents which are carried out in the context of the scientific solution of actual professional and pedagogical tasks is given. The list of research actions for each of three levels of high school education - a bachelor degree, a magistracy and postgraduate study is defined. Practical significance. The proposed criteria and diagnostic tools can be used in work of higher education for monitor tracking the quality of learners training to research activity.